MENGELOLA LEMBAGA PENDIDIKAN DI ERA GLOBAL (Pergeseran Paradigma Humanis Menjadi Bisnis) - Efferi, Adri (Pascasarjana IAIN Kudus, 2015)
Globalization is like a two-sided coin that each piece has its own role, meaning that globalization has led to remarkable progress in human civilization, but at thesame time is also not a few negative effects caused by the advent of globalization.We take the example that occurred in education today. Globalization that is characterized by ease of access to information, has caused a tremendous leap.Important discoveries were created in education such as teaching methods, curricula, media and others, so easily dispersed in a short time even within minutes and even seconds. But on the other hand, globalization also brings negative effect nor simple, for example in the management of educational institutions, there has been a paradigm shifting which originally humanist (humanity), into the calculations of profit and loss (business)